Wellbeing of gay fathers with children born through surrogacy: a comparison with lesbian-mother families and heterosexual IVF parent families. Issue 1 (14th November 2017) - Van Rijn-van Gelderen, L; Bos, H W M; Jorgensen, T D; Ellis-Davies, K; Winstanley, A; Golombok, S; Rubio, B; Gross, M; Vecho, O; Lamb, M E
Abstract: STUDY QUESTION: Are there differences in levels of parental wellbeing (parental stress, psychological adjustment and partner relationship satisfaction) between gay-father families with infants born through surrogacy, lesbian-mother families with infants born through donor insemination, and heterosexual-parent families with infants born through IVF? SUMMARY ANSWER: There were no differences in parental wellbeing. WHAT IS KNOWN ALREADY: The only other study of parental wellbeing in gay-father families formed through surrogacy (mean age children: 4 years old) found no difference in couple relationship satisfaction between these families and lesbian-mother families formed through donor insemination and heterosexual-parent families formed without assisted reproductive technologies. STUDY DESIGN, SIZE, DURATION: This cross-sectional study is part of an international research project involving 38 gay-father families, 61 lesbian-mother families and 41 heterosexual-parent families with 4-month-olds. In each country (the UK, the Netherlands and France), participants were recruited through several sources, such as specialist lawyers with expertise in surrogacy (for the recruitment of gay fathers), lesbian and gay parenting support groups, fertility clinics (for the recruitment of lesbian and heterosexual parents), and/or online forums and magazines. PARTICIPANTS/MATERIALS, SETTING, METHODS: During a home visit when their infants were between 3.5 and 4.5 months old, participants completed standardized measures of parental stress, parental psychological adjustment (anxiety and depression) and partner relationship satisfaction. MAIN RESULTS AND THE ROLE OF CHANCE: All parents reported relatively low levels of parental stress, anxiety and depression, and were all relatively satisfied with their intimate relationships. After controlling for caregiver role (primary or secondary caregiver role), there were no significant family type differences in parental stress, P = 0.949, depression, P = 0.089, anxiety, P = 0.117, or relationship satisfaction, P = 0.354. LIMITATIONS, REASONS FOR CAUTION: The findings cannot be generalized to all first-time ART parents with infants because only families from relatively privileged backgrounds participated. WIDER IMPLICATIONS OF THE FINDINGS: Our findings may have implications for the development of policy and legislation in relation to these new family forms, as well as the regulation of surrogacy in the Netherlands and France. In addition, our findings might encourage professional organizations of obstetricians and gynecologists in these countries to recommend that requests for assisted reproduction should be considered regardless of the applicants' sexual orientation. STUDY FUNDING/COMPETING INTEREST(S): This research was supported, under the auspices of the Open Research Area (Application BO 3973/1-1; Principal Investigator, Michael E Lamb), by grants from the UK Economic and Social Research Council (ESRC; Grant ES/K006150/1; Principal Investigator, Michael E. Lamb), The Netherlands Organisation for Scientific Research (NWO; Grant NWO 464-11-001, Principal Investigator, Henny W.M. Bos) and the French Agence Nationale de Recherche (ANR; Grant ANR-12-ORAR-00005-01, Principal Investigator, Olivier Vecho) whose support is gratefully acknowledged. There were no competing interests.